Expeditionary Force Capability: Improving the Brazilian Military - Lange, Valério Luiz (Centro de Estudos Estratégicos do Exército: Artigos Estratégicos, 2017)
This paper intends to bring a strategic perspective about the current military Expeditionary Force (EF) concept under development by the Brazilian Army and its contributions to improving Brazilian military capacity. Brazilian interests, national policies, and strategies are presented as references to the fields of domestic and international relations. An overview of the interaction between foreign and defense policies is shown in relation to the Brazilian interests in support of the concept of force projection. The present definition of EF is explained as it has been studied in the Brazilian Army. In the sequence, diplomatic, military, and economic elements of the Brazilian national power are presented to better understand the strategic context of an EF. The narrative also presents an expeditionary employment option under a United Nations’ peacekeeping mission framework to illustrate a likely use of this military capability, as well as some of the author’s recommendations to better organize a contemporary EF in Brazil.